Simulations in Social Work and Geriatrics - Tóth, Anikó Panna; R. Fedor, Anita (Magyar Gerontológia, 2024)
In the training of social work students and in the continuing education of social, mental health and medical professionals there is a wide range of opportunities to use simulation techniques. Simulation can be described as “a pedagogy using a real-world problem in a realistic environment to promote critical thinking, problem solving, and learning”.